Traditional food-processing and preparation practices to enhance the bioavailability of micronutrients in plant-based diets - Hotz, Christine; Gibson, Rosalind S. (Elsevier, 2007)
Dietary quality is an important limiting factor to adequate nutrition in many resource-poor settings. One aspect of dietary quality with respect to adequacy of micronutrient intakes is bioavailability. Several traditional household food-processing and preparation methods can be used to enhance the bioavailability of micronutrients in plant-based diets. These include thermal processing, mechanical processing, soaking, fermentation, and germination/malting. These strategies aim to increase the physicochemical accessibility of micronutrients, decrease the content of antinutrients, such as phytate, or increase the content of compounds that improve bioavailability. A combination of strategies is probably required to ensure a positive and significant effect on micronutrient adequacy. A long-term participatory intervention in Malawi that used a range of these strategies plus promotion of the intake of other micronutrient-rich foods, including animal-source foods, resulted in improvements in both hemoglobin and lean body mass and a lower incidence of common infections among intervention compared with control children. The suitability of these strategies and their impact on nutritional status and functional health outcomes need to be more broadly assessed.